2001
DOI: 10.1002/hon.667
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of normal and leukemic stem cell biology in Chronic Myeloid Leukemia

Abstract: Chronic Myeloid Leukemia (CML), a myeloproliferative disease of stem cell origin, is characterized by the presence of the Philadelphia (Ph) chromosome and the bcr-abl oncogene. The BCR-ABL fusion gene product, thought to be causative in CML, has multiple effects on diverse cell functions such as growth, differentiation and turnover as well as adhesion and apoptosis. Persistent Ph-negative progenitors co-exist with leukemic cells, both in the marrow and blood of patients, in the early chronic phase of the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…More is known about the molecular cell biology of this oncogene than any other associated with leukemia. The ABL (c-abl oncogene 1) proto-oncoprotein exists in the nucleus, bound to chromatin, and in the cytoplasm, co-localized with F-actin [57]. BCR/ABL is found in the cytoplasm predominantly.…”
Section: Bcr/ablmentioning
confidence: 99%
“…More is known about the molecular cell biology of this oncogene than any other associated with leukemia. The ABL (c-abl oncogene 1) proto-oncoprotein exists in the nucleus, bound to chromatin, and in the cytoplasm, co-localized with F-actin [57]. BCR/ABL is found in the cytoplasm predominantly.…”
Section: Bcr/ablmentioning
confidence: 99%
“…The majority of normal HSCs are a quiescent cell population stabilized in the G 0 stage of the cell cycle, with each cell cycling every 1-3 months. 122,123 It has been shown that CML develops as a consequence of characteristic changes within the HSCs. Almost all neoplastic clones carry the cytogenetic abnormality, Ph, and the fusion oncogene, Bcr-Abl.…”
Section: "Quiescent" CML Stem Cellsmentioning
confidence: 99%
“…Our experiments do not, however, address the mechanism whereby CML cells survive and proliferate when deprived of growth factor. This property is inevitably linked to the BCR/ABL oncogene, 10,15,29 and several molecular mechanisms have been proposed to explain the growth and survival of CML cells in low growth factor concentrations. 15,24,[29][30][31][32] Nevertheless, the in vivo action of increased elastase within the bone marrow of CML patients may explain several features of CML pathophysiology:…”
Section: Discussionmentioning
confidence: 99%